A Review on Piezoelectric, Magnetostrictive, and Magnetoelectric Materials and Device Technologies for Energy Harvesting Applications. Issue 5 (21st November 2017) - Narita, Fumio; Fox, Marina
Abstract : In the coming era of the internet of things (IoT), wireless sensor networks that monitor, detect, and gather data will play a crucial role in advancements in public safety, human healthcare, industrial automation, and energy management. Batteries are currently the power source of choice for operating wireless network devices due to their ease of installation; however, they require periodic replacement due to capacity limitations. Within the scope of the IoT, battery maintenance of the trillion sensor nodes that may be implemented will be practically infeasible from environmental, resource, and labor cost perspectives. In considering individual self‐powered sensor nodes, the idea of harvesting energy from ambient vibrations, heat, and electromagnetic waves has recently triggered noticeable research interest in the academic community. This paper gives an overview of energy harvesting materials and systems. Three main categories are presented: piezoelectric ceramics/polymers, magnetostrictive alloys, and magnetoelectric (ME) multiferroic composites. State‐of‐the‐art harvesting materials and structures are presented with a focus on characterization, fabrication, modeling and simulation, and durability and reliability. Some perspectives and challenges for the future development of energy harvesting materials are also highlighted. Abstract : Recent progress in piezoelectric ceramics/polymers, magnetostrictive alloys, and magnetoelectric (ME) multiferroic composites for energy harvesting applications is systematically summarized. A survey of the challenges in characterization, fabrication, modeling and simulation, and durability and reliability is presented.